2017
DOI: 10.1371/journal.pone.0184766
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of renal function in routine care of people living with HIV on ART in a resource-limited setting in urban Zambia

Abstract: IntroductionData on renal impairment in sub-Saharan Africa (SSA) remains scarce, determination of renal function is not part of routine assessments. We evaluated renal function and blood pressure in a cohort of people living with HIV (PLWH) on antiretroviral treatment (ART) in the Renal Care Zambia project (ReCaZa).MethodsUsing routine data from an HIV outpatient clinic from 2011–2013, we retrospectively estimated the glomerular filtration rate (eGFR, CKD-Epi formula) of PLWH on ART in Lusaka, Zambia. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
0
16
1
1
Order By: Relevance
“…Fifteen report overall safety of TDF in ART regimens, recommending its continued use with monitoring [2831, 37–40, 42, 44, 46, 4850]. Although the definitions of renal dysfunction differed widely, the other 16 studies report either statistical or clinical association of TDF with renal dysfunction [15, 22–26, 3235, 43, 45, 47, 51–53]. Groups at higher risk include patients with impaired renal function at baseline, older age groups and women [33, 35, 47].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen report overall safety of TDF in ART regimens, recommending its continued use with monitoring [2831, 37–40, 42, 44, 46, 4850]. Although the definitions of renal dysfunction differed widely, the other 16 studies report either statistical or clinical association of TDF with renal dysfunction [15, 22–26, 3235, 43, 45, 47, 51–53]. Groups at higher risk include patients with impaired renal function at baseline, older age groups and women [33, 35, 47].…”
Section: Resultsmentioning
confidence: 99%
“…Although some recommend monitoring of patients particularly those with deranged renal function parameters at baseline, there is, no consensus on recommended monitoring strategies to this end. On the other hand, 16 studies reported an association with seven of these reporting the association as significant (Table 3) [15, 22–26, 3235, 43, 45, 47, 51–53]. Five of the seven were done in Southern Africa [25, 34, 35, 43, 45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital-based studies from a National Referral Hospital in Uganda show that most patients with kidney disease are young and have advanced disease by the time of presentation 10 . Thus, in sub-Saharan Africa estimates of kidney disease prevalence vary widely depending on the methods used to determine renal function and the population studied, in particular the age distribution 8, 11– 19 .…”
Section: Introductionmentioning
confidence: 99%
“…These advances have permitted early measurement of key biological variables (biomarkers) with great accuracy, as well as minimal cost and resource investment. 3 Such devices permit the assessment of renal function in people living with HIV in resource-limited settings in urban Zambia, 4 cost-effective screening for CKD among Canadian indigenous peoples, 5 and early detection of kidney disease in Australia. 6 Using volunteer research students and technological innovation, including GPS, digital photography, and POC biochemical analysis, these devices have measured, for the first time, the burden of CKD and other public health priorities in Rivas, Nicaragua.…”
mentioning
confidence: 99%